PENGARUH INDEKS PEMBANGUNAN MANUSIA TERHADAP TINGKAT PENGANGGURAN DI PROVINSI BANTEN - Dwi Mahroji; Iin Nurkhasanah (FEB Universitas Sultan Ageng Tirtayasa, 2019)
The purpose of the study is to determine the effect of Human Development Index (HDI) investment and District Minimum Wage (MSE) to the unemployment rate in Banten Province and to determine the effect of Human Development Index (HDI), investment and District Minimum Wage (MSE) collectively to the unemployment rate in Banten Province. The method used in this research is panel data analysis method with Fixed Effect Model approach. The result of panel data analysis showed that the variable of Human Development Index (HDI) has significant and negative effect on 5% level to unemployment rate, investment variable has negative and significant effect on 5% level to unemployment rate, District Minimum Wage (MSE) has negative effect and significant at 5% level to unemployment rate and collectively variable of Human Development Index (HDI), investment and District Minimum Wage (MSE) have significant effect to unemployment rate in Banten Province.